2021
DOI: 10.1016/j.mad.2021.111575
|View full text |Cite
|
Sign up to set email alerts
|

Brain aging mechanisms with mechanical manifestations

Abstract: Brain aging is a complex process that affects everything from the subcellular to the organ level, begins early in life, and accelerates with age. Morphologically, brain aging is primarily characterized by brain volume loss, cortical thinning, white matter degradation, loss of gyrification, and ventricular enlargement. Pathophysiologically, brain aging is associated with neuron cell shrinking, dendritic degeneration, demyelination, small vessel disease, metabolic slowing, microglial activation, and the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 303 publications
(421 reference statements)
3
62
0
10
Order By: Relevance
“…In the DNN model, the subjects' age was the most important variable in estimating the GM-BHQ. These results are consistent with those of previous studies demonstrating that aging plays the most important role in cerebral atrophy ( 28 , 29 ). In addition, our recent studies have shown that there is a strong negative correlation between subjects' age and cognitive function, as represented by the MMSE score ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the DNN model, the subjects' age was the most important variable in estimating the GM-BHQ. These results are consistent with those of previous studies demonstrating that aging plays the most important role in cerebral atrophy ( 28 , 29 ). In addition, our recent studies have shown that there is a strong negative correlation between subjects' age and cognitive function, as represented by the MMSE score ( 1 ).…”
Section: Discussionsupporting
confidence: 93%
“…Aging is associated with specific alterations in signal transduction pathways, which culminates in memory impairments 43 . To detect the molecular and cellular mechanisms underlying this physiological event is a big challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Each brain's morphology is unique, and aging changes brain morphology in both healthy and pathological conditions ( 26 ). Heart failure, atrial fibrillation, and renal insufficiency may contribute to acute stroke with increasing age, especially in patients over 85 years of age ( 27 ).…”
Section: Discussionmentioning
confidence: 99%